Islamic Values Analysis in Emotional Regulation of Adult Women Involved in Physical - Karni, Asniti; Asvio, Nova; Sa’adah, Diana Zumrotus; Mindani, (Islam Transformatif : Journal of Islamic Studies, 2025)
Abstract Many adult women consider maintaining a healthy life through physical activities because help to release and control the emotion. However, there is no recent research about integrating Islamic values into physical and emotional for adult Muslim women. Based on the explanation, demonstrating how physical and spiritual aspects involve emotion is important. This study aims to explore the description of emotional regulation and analyze Islamic values ​​in the emotional regulation of adult women involved in physical fitness activities. Five informants were involved in this study. The data collection methods were in a form of observation, interviews, and documentation focused on strategy, negative emotions, control, and emotional responses. Data were analyzed using Miles and Huberman's analysis techniques to identify themes related to Islamic values ​​and emotional regulation. The results showed that physical fitness activities can potentially increase positive emotional regulation and physical health in adult women. Islamic values help participants face emotional challenges, increase self-awareness, and develop adaptive coping strategies. This study also found that physical fitness can allow adult women to apply Islamic values ​​in everyday life. Specifically, the gym trainer and the members can pray before training activities, meditate, practice patience, ask for forgiveness, and perform gratitude exercises. Moreover, the implication of this study is the importance of integrating Islamic values ​​in physical fitness programs, such as patience training, gratitude to Allah, surrendering to Allah, guarding gaze and tongue, sincerity and modesty by providing women-only sessions to support the emotional well-being of adult Muslim women. Abstrak Banyak wanita dewasa menyadari pentingnya menjaga kesehatan melalui aktivitas fisik karena membantu melepaskan dan mengendalikan emosi. Namun, belum ada penelitian tentang pengintegrasian nilai Islam ke dalam aspek fisik dan emosional bagi wanita muslim dewasa. Hal ini menunjukkan peran aspek fisik dan spiritual dalam regulasi emosi penting untuk diteliti. Penelitian ini bertujuan mengeksplorasi deskripsi regulasi emosi dan menganalisis nilai Islam dalam regulasi emosi wanita dewasa yang terlibat dalam aktivitas kebugaran jasmani dengan melibatkan lima informan Metode pengumpulan data berupa observasi, wawancara, dan dokumentasi yang difokuskan pada strategi, emosi negatif, kontrol, dan respons emosional. Data dianalisis dengan teknik analisis Miles dan Huberman untuk mengidentifikasi tema-tema yang terkait dengan nilai Islam dan regulasi emosi. Hasil penelitian menunjukkan bahwa aktivitas kebugaran jasmani berpotensi meningkatkan regulasi emosi positif dan kesehatan fisik pada wanita dewasa. Nilai Islam membantu partisipan menghadapi tantangan emosional, meningkatkan kesadaran diri, dan mengembangkan strategi pengendalian emosi yang adaptif. Kebugaran jasmani dapat memungkinkan wanita dewasa menerapkan nilai Islam dalam kehidupan sehari-hari. Secara khusus, pelatih dan anggota berdoa sebelum latihan, bermeditasi, melatih kesabaran, memohon ampunan (istighfar), dan melatih rasa syukur. Implikasi penelitian ini adalah pentingnya mengintegrasikan nilai Islam dalam program kebugaran jasmani, seperti latihan kesabaran, rasa syukur, berserah diri kepada Allah, menjaga pandangan dan lisan, keikhlasan dan kesopanan dengan menyediakan sesi khusus wanita untuk mendukung kesehatan emosional wanita muslim dewasa.